2022
DOI: 10.1016/j.tplants.2021.11.003
|View full text |Cite
|
Sign up to set email alerts
|

TALE-induced cell death executors: an origin outside immunity?

Abstract: Phytopathogenic bacteria inject effector proteins into plant host cells to promote disease. Plant resistance (R) genes encoding nucleotide-binding leucine-rich repeat (NLR) proteins mediate the recognition of functionally and structurally diverse microbial effectors, including transcription-activator like effectors (TALEs) from the bacterial genus Xanthomonas. TALEs bind to plant promoters and transcriptionally activate either disease-promoting host susceptibility (S) genes or cell death-inducing executor-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 64 publications
(82 reference statements)
3
18
0
Order By: Relevance
“…Transcription activator-like effectors (TALEs), are a recent hotspot in executor gene discovery that can provide methods to regulate resistance. In Xanthomonas , TALEs can bind to effector binding elements (EBEs) in promoters of host plants and activate expression of host susceptibility ( S ) genes and R genes [ 147 ]. Tomato Bs4 (bacterial spot resistance locus no.…”
Section: Novel Strategies To Activate Defense Responses In Horticultu...mentioning
confidence: 99%
“…Transcription activator-like effectors (TALEs), are a recent hotspot in executor gene discovery that can provide methods to regulate resistance. In Xanthomonas , TALEs can bind to effector binding elements (EBEs) in promoters of host plants and activate expression of host susceptibility ( S ) genes and R genes [ 147 ]. Tomato Bs4 (bacterial spot resistance locus no.…”
Section: Novel Strategies To Activate Defense Responses In Horticultu...mentioning
confidence: 99%
“…Under natural conditions, infection, colonization, and reproduction of Xanthomonas on host plants mainly depend on the activation of host susceptibility ( S ) genes by TALEs secreted by Xanthomonas , while other genes targeted by TALEs tend to be off-target ( Nowack et al, 2021 ). Since PH has no TALE genes, it is unable to promote the expression of S genes, and this would affect its viability in rice leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we speculate that IP‐L serves as the crossing point between virus and host, and is the game field of virus infection against host resistance. The plant recognizes the virus through IP‐L to activate the defense response, while the virus hijacks IP‐L to reduce host resistance (Liu et al., 2022; Nowack et al., 2021), which indicates that IP‐L is a protein with dual functions. In the present study, we found that IP‐L could inhibit the expression of NbCML30 at the nucleic acid and protein levels (Figure 5a–j).…”
Section: Discussionmentioning
confidence: 99%